A Glimpse from the Chambord Staircase at Translation’s Role in Comparative Literature - Koustas, Jane (TTR, 2009)
While the importance of the translation process remains recognized as a worthwhile activity in both Literary/Cultural Studies and in fiction, it is frequently overlooked in larger discussions of Canadian literature, including comparative studies. Such activities aim to blur the lines between Us and Them, between Other and Self, or between the Rest of Canada (the Roc) and Quebec, in other words, to align or combine the frequently cited legendary two staircases of Château de Chambord. However, in the process, they have obscured other boundaries, such as those between Comparative Literature and Translation. Studies in Comparative Canadian Literature, for example, frequently overlook, or at least downplay, the importance of translation, neglecting to consider, for example, the translation strategy used and the selection of translated works available for comparison.